(3EOGQI GdCaQGO (B/s - (3Rhjda, egOj MSfs ((3YeGf(B: s (3ecJHI GdeLJeY GdYQHj(B, s, 2010)
(3eaghe EOGQI GdGaQGO JWhQgG hhXGFagG h CgOGagG h YdGbJgG HGdGOGQGJ GdGNQi, JMdjd h JhUja GdYed, JNWjW Gdbhi GdYGedI, eUGOQ GdMUhd Ydi GdehGQO GdHTQjI, GdGNJjGQ h GdJYjjf h Jcjja GdYGedjf, CSGSjGJ aj GdJOQjH h JMOjO GdMGLGJ GdJOQjHjI, WQb GdJOQjH h Jbjeg, fXe GdGLhQ h GdQhGJH, GdMhGaR h GdOhGaY, Jbjje COGA GdYGedjf, EfVHGW GdCaQGO, GdSdGeI GdYeGdjI, GdJTQjYGJ GdYeGdjI h GdJLQHI GdCQOfjI h CNjQG GdYdGbGJ GdUfGYjIs
Keywords: (3EOGQI GdCaQGOs; (3GdEOGQIs; (3Gdbhi GdYGedIs